2023
DOI: 10.3847/2041-8213/acf4e3
|View full text |Cite
|
Sign up to set email alerts
|

The Dusty Red Supergiant Progenitor and the Local Environment of the Type II SN 2023ixf in M101

Zexi Niu,
Ning-Chen Sun,
Justyn R. Maund
et al.

Abstract: As one of the closest supernovae (SNe) in the last decade, SN 2023ixf is an unprecedented target to investigate the progenitor star that exploded. However, there is still significant uncertainty in the reported progenitor properties. In this work, we present a detailed study of SN 2023ixf’s progenitor with two independent analyses. We first modeled its spectral energy distribution (SED) based on Hubble Space Telescope optical, Spitzer mid-infrared (IR), and ground-based near-IR data. We find that stellar pulsa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 60 publications
4
22
3
Order By: Relevance
“…To constrain the properties of the progenitor of SN 2023ixf, SEDs of the progenitor are presented by a number of authors (e.g., Jencson et al 2023;Kilpatrick et al 2023;Neustadt et al 2024;Niu et al 2023;Soraisam et al 2023;Xiang et al 2024). Detections in Spitzer channel 1 and channel 2, MMT J, Gemini/NIRI J, UKIRT JHK, and Hubble Space Telescope (HST) F814W and F675W are used here.…”
Section: Progenitor Analysis Via Stacked Datamentioning
confidence: 99%
See 1 more Smart Citation
“…To constrain the properties of the progenitor of SN 2023ixf, SEDs of the progenitor are presented by a number of authors (e.g., Jencson et al 2023;Kilpatrick et al 2023;Neustadt et al 2024;Niu et al 2023;Soraisam et al 2023;Xiang et al 2024). Detections in Spitzer channel 1 and channel 2, MMT J, Gemini/NIRI J, UKIRT JHK, and Hubble Space Telescope (HST) F814W and F675W are used here.…”
Section: Progenitor Analysis Via Stacked Datamentioning
confidence: 99%
“…The discovery of SN 2023ixf led to a sustained spectroscopic and photometric follow-up effort (e.g., Berger et al 2023;Bostroem et al 2023;Jacobson-Galán et al 2023;Sgro et al 2023;Smith et al 2023). To date, these multiwavelength follow-up observations and archival data examination have revealed detections of a dusty RSG progenitor and signatures of interaction with circumstellar material (e.g., Berger et al 2023;Bostroem et al 2023;Grefenstette et al 2023;Guetta et al 2023;Hiramatsu et al 2023;Jacobson-Galán et al 2023;Jencson et al 2023;Kilpatrick et al 2023;Koenig 2023;Kong 2023;Li et al 2023;Neustadt et al 2024;Niu et al 2023;Panjkov et al 2023;Pledger & Shara 2023;Qin et al 2023;Sarmah 2023;Singh Teja et al 2023;Smith et al 2023;Soraisam et al 2023;Van Dyk et al 2023;Vasylyev et al 2023;Xiang et al 2024;Yamanaka et al 2023;Zhang et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The preexplosion images have revealed the progenitor star to be a red supergiant in a dusty region (Jencson et al 2023;Kilpatrick et al 2023;Soraisam et al 2023;Van Dyk et al 2023). Several groups have constrained the mass of the progenitor, which have resulted so far in a large mass range within 8-20 M e (Jencson et al 2023;Kilpatrick et al 2023;Niu et al 2023;Pledger & Shara 2023;Soraisam et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Soraisam et al (2023) found a mass-loss rate of (2-4) × 10 −4 M e yr −1 using 19 yr of archival IR data, which was also obtained by Grefenstette et al (2023) in their X-ray NuSTAR measurements. On the lower end, Jencson et al (2023) and Niu et al (2023) estimated it to be (3-30) × 10 −5 M e yr −1 , and 10 −5 M e yr −1 , respectively, in 3-20 yr before explosion. The metallicity has ranged between half the solar (Niu et al 2023) to solar (Van Dyk et al 2023;Zimmerman et al 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation